Quantitative approaches for evaluating the influence of films using the IMDb database (Communication & Society, 2016)
Why do films certain remain influential throughout filmhistory? The purpose of this paper is to attempt to answer thisquestion. To do so, we adopt some quantitative approaches thatfacilitate an objective interpretation of the data. The data sourcewe have chosen for this study is the Internet Online MovieDatabase (IMDb), and in particular, one of its sections called"Connections", which lists references made to a film insubsequent movies and references made in the film itself toprevious ones. The extraction and analysis of these networks ofcitations allows us to draw some conclusions about the mostinfluential movies in film history, identifying theirdistinguishing features, and considering how their popularityhas evolved over time.